A lithium-ion battery silicon-carbon negative electrode material and preparation method thereof

By using a core shell structure silicon carbon composite material in the negative electrode material of lithium ion battery, combined with self -association assembly and pressure treatment technology, a dense and perforated conductive network structure is formed. The problem of capacity attenuation during the cycle is solved, and the high -ratio energy and good cycle stability are achieved, and the production cost is reduced.

CN113964307BActive Publication Date: 2025-01-28JIANGSU E ONTECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111236998.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-24
Publication Date
2025-01-28
Estimated Expiration
2041-10-24

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode material has rapidly attenuated capacity due to the volume expansion of silicon and internal reaction during the circulation process, making it difficult to take into account high specific energy, fast electron and ion transmission rates, good cycle stability and low production costs.

Method used

The silicon carbon composite electrode material with a core shell structure is used. The kernel contains silicon nanoparticles, graphite nanims, one -dimensional conductive materials, and unspecified carbon. The shell is carbon coated layer. The conductive network structure of the hole is covered with a smooth and uniform carbon coating layer outside the material.

Benefits of technology

The high -ratio energy (reversible than 1100mAh/g), high efficiency and circulation stability (50 % capacity retention rates greater than 90 %), while reducing the preparation cost and simplifying the process process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113964307B_ABST
    Figure CN113964307B_ABST
Patent Text Reader

Abstract

The present invention relates to a silicon-carbon negative electrode material for lithium-ion batteries. The silicon-carbon negative electrode material is a dense and non-porous core-shell structure, the core of which includes nano-silicon, carbon nanotubes, amorphous carbon and nano-graphite sheets, and the shell of which is a carbon coating layer. The present invention mainly forms a dense and non-porous structure with a conductive network inside the material by combining self-crosslinking assembly, pressure treatment and carbonization coating, wherein nano-silicon, carbon nanotubes and amorphous carbon are tightly embedded between the sheets of uniformly dispersed nano-graphite sheets, thereby achieving a dense structure, promoting electron transmission, and also buffering the expansion of the internal material. The smooth and uniform carbon coating layer outside the material can reduce the formation of silicon exposed on the surface and SEI film. The material has excellent cycle performance and rate performance, and can meet the needs of high specific energy lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion battery negative electrode materials, and in particular to a lithium ion battery silicon-carbon negative electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high output voltage, high specific energy, long cycle life, and good safety performance. They have been widely used in mobile communications, laptops, future electric vehicles, and other fields, gradually replacing traditional chemical power sources such as lead-acid batteries. Especially with the increasing prominence of energy and environmental issues around the world, lithium-ion batteries have become the focus of development in the field of new energy materials.

[0003] For lithium-ion batteries, the performance of positive and negative electrode materials directly determines the performance of the battery. In terms of negative electrode materials, natural graphite materials have the advantages of abundant reserves, low price, high specific capacity and low voltage platform, and have become the negative electrode materials used in traditional lithium-ion batteries. However, this type of graphite carbon material has a low theoretical capacity (only 372mAh / g), which drives the lithium-ion battery engineering community to look for a new generation of electrode materials with high energy density.

[0004] Elemental silicon has attracted more and more attention as a negative electrode material due to its very high theoretical specific capacity. It is considered to be one of the most likely materials to replace graphite negative electrodes. However, silicon will produce about 300% volume expansion / contraction during the lithium insertion / extraction process, which can easily cause material agglomeration or powderization during the cycle process, resulting in rapid capacity decay, and therefore cannot meet practical needs.

[0005] In order to avoid the shortcomings of the above two types of materials, researchers have taken a variety of measures to combine the two to achieve the purpose of complementary advantages. Patent CN 103474667 B discloses a core-double-shell composite lithium-ion battery negative electrode material composed of nano-silicon / graphite particles as the core, carbon nanotubes and / or amorphous carbon as the first carbon coating layer and an organic cracked carbon layer, and its preparation method. The composite material effectively improves the ion conductivity, and can effectively control the volume change of silicon during the charge and discharge process, while also reducing the reaction between the internal silicon and the electrolyte. The material has excellent rate charge and discharge performance and good cycle life, but due to the insufficient bonding strength between the loose carbon source part of the internal structure and the silicon material, the two are not evenly composited, and the energy density and cyclic conductivity of this material still need to be further improved.

[0006] In summary, it is difficult for the composite carbon-silicon materials prepared in the prior art to have fast electron and ion transfer rates and good cycle stability while maintaining high specific energy, while also meeting low production costs and simple and environmentally friendly process flows. Summary of the invention

[0007] One of the purposes of the present invention is to provide a lithium ion battery silicon-carbon composite negative electrode material to improve the specific energy of the silicon-carbon composite negative electrode material and to have both higher cycle performance and rate performance.

[0008] A lithium-ion battery silicon-carbon negative electrode material has a core-shell structure, wherein the core contains silicon nanoparticles, graphite nanosheets, one-dimensional conductive materials and amorphous carbon; and the outer shell is a carbon coating layer.

[0009] The mass ratio of silicon nanoparticles, graphite nanosheets, one-dimensional conductive material and amorphous carbon is (1-50): (1-50): (1-20): (1-10).

[0010] The one-dimensional conductive material is carbon nanotubes; the diameter of the carbon nanotubes is 2-20 nm and the length is 1 to 30 μm.

[0011] The D50 particle size of the lithium-ion battery silicon-carbon composite negative electrode material is 8 to 24 μm, and the specific surface area is 1.3 m 2 / g~6.8m 2 / g, compacted density is 1.0g / cm 3 ~1.8g / cm 3 .

[0012] A method for preparing a lithium-ion battery silicon-carbon negative electrode material comprises the following steps:

[0013] Step 1, dispersing nanographite sheets and a cross-linking agent in an organic solvent to perform a cross-linking reaction;

[0014] Step 2, adding nano silicon particles, a one-dimensional conductive material, and a first carbon source to the dispersion obtained in step 1, mixing evenly, evaporating the solvent, and applying pressure to obtain a silicon-carbon polymer;

[0015] Step 3, calcining and crushing the silicon-carbon polymer;

[0016] Step 4: coating with a second carbon source to obtain a negative electrode material.

[0017] The one-dimensional conductive material is selected from carbon nanotubes; the diameter of the carbon nanotubes is 2-20nm and the length is 1-30μm.

[0018] The first carbon source includes, but is not limited to, any one or a combination of at least two of alkanes, cycloalkanes, olefins, alkynes, aromatic hydrocarbons, polymers, sugars, organic acids, and resin-based polymer materials. Other organic carbon sources commonly used for coating in the art can also be used in the present invention, preferably any one or a combination of at least two of methane, ethane, ethylene, phenol, asphalt, epoxy resin, phenolic resin, furfural resin, urea-formaldehyde resin, polyvinyl alcohol, polyvinyl chloride, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, acrylic resin, and polyacrylonitrile.

[0019] The mass ratio of the silicon nanoparticles, the nanographite sheets, the one-dimensional conductive material and the first carbon source is (1-50): (1-50): (1-20): (1-10).

[0020] The diameter of the nanographite sheet is 10 to 20 μm and the thickness is 50 to 100 nm.

[0021] In step 1, a pH buffer solution needs to be added to the organic solvent, and the pH buffer solution is a combination of one or more of acetic acid, ammonium acetate, potassium acetate, ammonia water, ammonium chloride, hypophosphorous acid, sodium hypophosphite, potassium hypophosphite, sodium carbonate or sodium bicarbonate; and the pH value is 5 to 10.

[0022] In step 1, the crosslinking agent is a silane crosslinking agent; the silane crosslinking agent is any one of dealcoholization silane, deacidification silane or deketoxime silane, or a combination of at least two of them.

[0023] The crosslinking agent is preferably a combination of one or more of methyltrimethoxysilane, vinyltriethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, triacetoxyethylsilane, propyltriacetoxysilane, n-heptyltrichlorosilane, octyltrichlorosilane, decyltrichlorosilane, dodecyltrichlorosilane, tetradecyltrichlorosilane, 1,8-bis(trichlorosilyl)octane, 1,10-bis(trichlorosilyl)decane, methyltributylacetoximate silane or vinyltributylacetoximate silane.

[0024] In step 1, the organic solvent is one or a combination of at least two of tetrahydrofuran, dimethylacetamide, C1-C6 alcohol and C3-C8 ketone, the C1-C6 alcohol is one or a combination of at least two of methanol, ethanol, ethylene glycol, propanol, isopropanol, 1,2-propylene glycol, 1,3-propylene glycol, glycerol, n-butanol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, n-pentanol and 2-hexanol, and the C3-C8 ketone is one or a combination of at least two of acetone, methyl ethyl ketone, methyl propyl ketone, N-methylpyrrolidone, ethyl propyl ketone, methyl butyl ketone, ethyl n-butyl ketone, methyl amyl ketone and methyl hexyl ketone.

[0025] In step 1, a constant temperature stirring device is used for heating and stirring, the heating temperature is 90-120° C., the stirring speed is 3000-6000 r / min, and the heating and stirring time is 2-5 h; the reaction process is carried out in an air environment with a humidity of 20%-60%.

[0026] In step 2, the D50 particle size of the nano silicon particles is 20 to 80 nm.

[0027] In step 2, the heating temperature of the mixing process is 40-60° C., the stirring speed is 2000-5000 r / min, and the mixing time is 2-4 h.

[0028] In step 2, evaporating the solvent adopts one or more of boiling drying, vacuum drying, spray drying, suction filtration drying, freeze drying, rotary drying, infrared drying, and microwave drying.

[0029] The spray drying is any one of two-fluid, gas-electric combined two-fluid, and four-fluid spray; preferably, when the spray drying is performed, the mixed liquid is charged into a closed spray drying device in the form of a spray, and a protective gas is charged into the closed spray drying device, and the protective gas is one or a combination of at least two of nitrogen, helium, argon, and neon; at the same time, the spray drying pressure is controlled to be 0.2-0.4Mpa, the inlet temperature is 100-250°C, the outlet temperature is 60-140°C, and the feed pump frequency of the spray drying equipment is 10-30Hz.

[0030] The vacuum drying adopts a vacuum drying machine with a condensation system, the temperature condition is 50-150° C., and the vacuum negative pressure does not exceed 0.1 Mpa.

[0031] The pressurization treatment in step 2 is one or a combination of at least two of extrusion molding treatment, cold molding treatment, hot molding treatment and hot isostatic pressing treatment.

[0032] Preferably, the hot isostatic pressing treatment is to place the dried product in a hot isostatic press, pressurize and heat it to 250-400°C at 60MPa-150MPa, keep it at this temperature for 1-3h, then turn off the power and cool it to room temperature with the furnace to obtain a silicon-carbon polymer.

[0033] Preferably, the cold molding process and the hot molding process are to control the compaction degree by controlling the mold filling ratio, that is, the ratio of the composite material mass to the mold volume; preferably, the hot molding process is to fill the dried product into the mold, wherein the mold filling ratio is 0.4-2.7 g / cm 3 The hot pressing temperature is 150-300°C, the pressing pressure is 5-30MPa, the hot pressing time is 30-100min, and the mixture is allowed to stand and cool to room temperature to obtain a silicon-carbon polymer.

[0034] Preferably, the extrusion forming process comprises feeding the dried product into a twin-screw machine or placing it in an internal mixer for primary compaction of the raw materials, and then performing a second compaction by a roller press to obtain a silicon-carbon polymer.

[0035] In step 3, during the calcination process, the temperature is first raised from room temperature to 300-400° C., kept warm for 1-2 hours, and then continued to be raised to 800-1000° C., and kept warm for 3-4 hours; the sintering is carried out in a vacuum furnace, a box furnace, a rotary kiln, a roller kiln, a push kiln or a tube furnace; the sintering process is carried out under a protective atmosphere, and the protective atmosphere is one or a combination of at least two of nitrogen, helium, argon and neon.

[0036] In step 3, during the crushing process, the silicon-carbon polymer is crushed and classified to obtain a silicon-carbon core material with a median particle size of 8 to 40 μm; preferably, the crushing is carried out in a crusher, and the crusher is selected from at least one of a turbine crusher, a jaw crusher and a Raymond mill.

[0037] In step 4, the coating method is selected from any one of a gas phase coating method, a liquid phase coating method or a solid phase coating method.

[0038] Preferably, the steps of the vapor coating method are: placing the silicon-carbon core material into a vapor deposition furnace, introducing a protective gas, then heating to 600-800°C, and calcining for 4-8 hours, during which time an organic carbon source gas is introduced for chemical vapor deposition for 1.5-2 hours, so that a smooth and uniform carbon coating layer can be coated on the outside of the material.

[0039] Preferably, the steps of the liquid phase coating method are: adding the silicon-carbon core material to a dispersed solvent containing a liquid phase coating carbon source, stirring and fusing, drying to obtain a coating, and then putting it into a furnace with a protective gas for sintering. The sintering temperature is 800 to 1000°C, and the high-temperature sintering time is 5 to 8 hours, so that a smooth and uniform carbon coating layer can be coated on the outside of the material.

[0040] Preferably, the steps of the solid phase coating method are: mixing the silicon-carbon core material with the coating organic carbon source and placing it in a coating machine for high-temperature solid phase coating to obtain a silicon-carbon solid phase coating material, and then putting the silicon-carbon solid phase coating material into a carbonization furnace, introducing a protective gas, the temperature of the carbonization furnace is 600-1200°C, the carbonization is carried out for 1.5-4h, and a smooth and uniform carbon coating layer is formed on the outer surface of the material after natural cooling.

[0041] Preferably, the protective gas is one or a combination of at least two of nitrogen, helium, argon and neon.

[0042] In step 4, the coated material needs to be refined and screened. The refinement method is one or a combination of at least two of mechanical crushing, air flow crushing or ball milling, and spheroidization treatment. The screening method is vibration screening, passing through a 200-mesh sieve, to obtain a silicon-carbon negative electrode material with a D50 particle size of 8 to 24 μm.

[0043] A lithium ion battery comprises the above-mentioned silicon-carbon negative electrode material.

[0044] Beneficial Effects

[0045] The silicon-carbon negative electrode material is assembled through self-crosslinking to form a three-dimensional conductive scaffold between nano-graphite sheets, and nano-silicon, carbon nanotubes and amorphous carbon are embedded between the graphite sheets. They are further tightly combined through pressure treatment, and a smooth and uniform carbon coating layer is coated on the outside of the material to obtain a silicon-carbon negative electrode material with a dense and pore-free core-shell structure inside.

[0046] Through a combination of self-crosslinking assembly, pressure treatment and carbonization coating, a dense non-porous structure with a conductive network is formed inside the material, in which nano-silicon, carbon nanotubes and amorphous carbon are tightly embedded in the interlayers of evenly dispersed nano-graphite sheets, achieving a dense and flexible structure, promoting electron transmission, and thus improving the specific energy of the material; at the same time, it also serves to buffer the expansion of the internal material. The smooth and uniform carbon coating on the outside of the material can reduce the exposed silicon on the surface and the formation of SEI film, making the material have a higher first efficiency and cycle stability.

[0047] The obtained silicon-carbon negative electrode material has a reversible specific capacity greater than 1100 mAh / g, a first cycle coulombic efficiency greater than 85%, a capacity retention rate greater than 90% after 50 cycles, low preparation cost, simple and controllable process, and is suitable for negative electrode materials of high-capacity lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a cross-sectional SEM image of the silicon-carbon composite negative electrode material for the lithium-ion battery of Example 1.

[0049] Figure 2 This is a cross-sectional SEM image of the silicon-carbon composite negative electrode material of the lithium-ion battery in Comparative Example 1.

[0050] Figure 3 This is a cross-sectional SEM image of the silicon-carbon composite negative electrode material of the lithium-ion battery in comparative example 2.

[0051] Figure 4 This is a compaction cycle curve diagram of the silicon-carbon composite negative electrode material for a lithium-ion battery in Example 1. DETAILED DESCRIPTION

[0052] Example 1

[0053] (1) 7 g of nanographite sheets, 2 g of octyltrichlorosilane and 10 g of sodium bicarbonate were added to 150 g of a mixed solution of methanol and isopropanol in a mass ratio of 4:1, and stirred using a constant temperature stirring device at a heating temperature of 100°C for 3 h at a speed of 4000 r / min to fully hydrolyze and condense the octyltrichlorosilane in the precursor solution to form a cross-linked product, polymerized silica gel. The reaction process is as follows:

[0054] 2nCH 3 (CH 2 ) 6 CH 2 SiCl 3 +3nH 2 O→[CH 3 (CH 2 ) 6 CH 2 SiO 3 Si(CH 2 ) 6 CH 3 ]n+6nHCl,

[0055] A dispersion of nanographite sheets with a three-dimensional cross-linked scaffold inside is obtained;

[0056] (2) Add 8 grams of nano-silicon particles, 4 grams of carbon nanotubes and 7 grams of asphalt to the prepared nano-graphite sheet dispersion, stir and mix in a disperser for 30 minutes at a speed of 2000 r / min to form a mixed solution; fill the mixed solution into a closed spray drying device in the form of a spray, and introduce nitrogen into the closed spray drying device, while controlling the pressure of the closed spray drying device to 0.2 MPa, the feed inlet temperature to 180°C, the discharge port temperature to 100°C, and the formed spray gas flow rate to 6.4 mL / min; place the dried product in a hot isostatic press, pressurize and heat it, and obtain three materials with different densities by adjusting different pressure values ​​(adjusting within the range of 50-100 MPa). The temperature of the pressurization process reaches 350°C, and after keeping the temperature and pressure for 2 hours, the power is turned off and the furnace is cooled to room temperature to obtain a silicon-carbon polymer;

[0057] (4) placing the silicon-carbon polymer in a box furnace, heating it to 300°C at a heating rate of 5°C / min, heat treatment holding time of 1 hour, and then continuing to heat it to 900°C at the same rate, holding it for 3.5 hours, and then naturally cooling it to room temperature, with nitrogen as protective gas during the whole process; crushing the sintered product in a Raymond mill, grading, and fine screening to obtain a silicon-carbon core material with a median particle size of 20 μm;

[0058] (5) The obtained silicon-carbon core material is dispersed in anhydrous ethanol, and sucrose accounting for 5% of the weight of the silicon-carbon core material is added. After being fully stirred for 1 hour, a spray drying method is used for secondary drying and granulation. The inlet temperature during spray drying is controlled to be 150°C, and the outlet temperature is controlled to be 80°C to obtain liquid-coated modified material particles; a ball mill is used to spheroidize the material particles, and the ball-milled material is sieved through a 200-mesh sieve. At the same time, the unsieved powder is continued to be ball-milled, and the iteration is repeated until all are sieved, and finally a silicon-carbon negative electrode material with a D50 particle size of 16 μm is obtained.

[0059] Example 2

[0060] The difference from Example 1 is that step (1):

[0061] 7 grams of nanographite sheets, 2 grams of n-heptyltrichlorosilane and 12 grams of sodium bicarbonate were added to 150g of a mixed solution of methanol and isopropanol in a mass ratio of 4:1, and stirred using a constant temperature stirring device. The heating temperature was 100°C, stirring was performed for 2.5 hours, and the speed was 4500r / min, so that the n-heptyltrichlorosilane in the precursor solution was fully hydrolyzed and condensed to form a cross-linked product, polymerized silica gel. The reaction process is as follows:

[0062] 2nCH 3 (CH 2 ) 5 CH 2 SiCl 3 +3nH 2 O→[CH 3 (CH 2 ) 5 CH 2 SiO 3 Si(CH 2 ) 5 CH 3 ]n+6nHCl,

[0063] A dispersion of nanographite sheets with a three-dimensional cross-linked scaffold inside is obtained;

[0064] The other process conditions were the same to prepare the silicon-carbon negative electrode material.

[0065] Example 3

[0066] The difference from Example 1 is that step (1):

[0067] 7 grams of nanographite sheets, 3 grams of decyltrichlorosilane and 10 grams of sodium bicarbonate were added to a 150g mixed solution of methanol and isopropanol in a mass ratio of 4:1, and stirred using a constant temperature stirring device. The heating temperature was 120°C, stirring was performed for 4 hours, and the speed was 3500r / min, so that the decyltrichlorosilane in the precursor solution was fully hydrolyzed and condensed to form a cross-linked product, polymerized silica gel. The reaction process is as follows:

[0068] 2nCH 3 (CH 2 ) 8 CH 2 SiCl 3 +3nH 2 O→[CH 3 (CH 2 ) 8 CH 2 SiO 3 Si(CH 2 ) 8 CH 3 ]n+6nHCl,

[0069] A dispersion of nanographite sheets with a three-dimensional cross-linked scaffold inside is obtained;

[0070] The other process conditions were the same to prepare the silicon-carbon negative electrode material.

[0071] Example 4

[0072] The difference from Example 1 is that step (1):

[0073] 7 grams of nanographite sheets, 4 grams of tetradecyltrichlorosilane and 8 grams of sodium bicarbonate were added to a 150g mixed solution of methanol and isopropanol in a mass ratio of 4:1, and stirred using a constant temperature stirring device. The heating temperature was 150°C, stirring was performed for 4.5 hours, and the speed was 4000r / min, so that the tetradecyltrichlorosilane in the precursor solution was fully hydrolyzed and condensed to form a cross-linked product, polymerized silica gel. The reaction process is as follows:

[0074] 2nCH 3 (CH 2 ) 11 CH 2 SiCl 3 +3nH 2 O→[CH 3 (CH 2 ) 11 CH 2 SiO 3 Si(CH 2 ) 11 CH 3 ]n+6nHCl,

[0075] A dispersion of nanographite sheets with a three-dimensional cross-linked scaffold inside is obtained;

[0076] The other process conditions were the same to prepare the silicon-carbon negative electrode material.

[0077] Example 5

[0078] The difference from Example 1 is that the hot isostatic pressing treatment in step (2) is changed to hot molding treatment, and the specific steps are as follows:

[0079] The dried product was filled into a mold, wherein the filling ratio of the mold was 1.5 g / cm3, the hot pressing temperature was 200°C, the pressing pressure was 20 MPa, the hot pressing time was 60 min, and the mold was allowed to cool to room temperature to obtain a silicon-carbon polymer.

[0080] The other process conditions were the same to prepare the silicon-carbon negative electrode material.

[0081] Example 6

[0082] The difference from Example 1 is that the liquid phase coating modification in step (4) is changed to gas phase coating modification, and the specific steps are:

[0083] The silicon-carbon core material is placed in a vapor deposition furnace, a protective gas is introduced, and then the temperature is raised to 700°C and the calcination time is 7 hours. During this period, an organic carbon source gas is introduced for chemical vapor deposition for 2 hours, and a smooth and uniform carbon coating layer can be coated on the outside of the material.

[0084] The other process conditions were the same to prepare the silicon-carbon negative electrode material.

[0085] Example 7

[0086] The difference from Example 1 is that the liquid phase coating modification in step (4) is changed to solid phase coating modification, and the specific steps are:

[0087] The silicon-carbon core material is mixed with the coating organic carbon source and placed in a coating machine for high-temperature solid-phase coating to obtain a silicon-carbon solid-phase coating material. The silicon-carbon solid-phase coating material is then put into a carbonization furnace and a protective gas is introduced. The temperature of the carbonization furnace is 800°C and the carbonization is carried out for 3 hours. After natural cooling, a smooth and uniform carbon coating layer is formed on the outer surface of the material.

[0088] The other process conditions were the same to prepare the silicon-carbon negative electrode material.

[0089] Comparative Example 1: No crosslinking agent added

[0090] The difference from Example 1 is that steps (1) and (2):

[0091] 8 grams of nano-silicon particles, 4 grams of carbon nanotubes, 7 grams of nano-graphite sheets and 10 grams of asphalt were added to 150 g of a mixed solution of methanol and isopropanol in a mass ratio of 4:1, and stirred in a disperser for 30 minutes at a speed of 2000 r / min to form a mixed solution; subsequently, drying and hot isostatic pressing were performed in the same manner as in Example 1.

[0092] The other process conditions were the same to prepare the silicon-carbon negative electrode material.

[0093] Comparative Example 2: No pressure treatment

[0094] The difference from Example 1 is that after the mixed liquid is spray-dried in step (2), no pressure treatment is performed and the sintering and carbonization in step (3) is directly performed.

[0095] The other process conditions were the same to prepare the silicon-carbon negative electrode material.

[0096] Electrochemical performance test

[0097] The electrochemical performance of the above silicon-carbon composite negative electrode material was evaluated by assembling it into a CR2032-button half-cell. The button cell production process is as follows: the mass ratio of active material (Si / C), acetylene black, CMC, and SBR is 80:10:4:6, of which CMC is a 1% aqueous solution. Use a high-speed shear mixer at 10000rpm to disperse the slurry for 30min. Then evenly coat the stirred slurry on a 15μm thick copper foil. After natural drying, place the copper foil in a vacuum drying oven at 80℃ for 10h, and compact the dried copper foil with a roller press; punch and cut the pole piece into a disc with a diameter of 13mm. The half-cell was assembled in a glove box protected by high-purity argon gas. The electrode was made of metal lithium foil, the diaphragm was made of polypropylene porous membrane, and the electrolyte was 1M LiPF6. 1M LiPF6 and 5wt% fluoroethylene carbonate were added to the mixed solution of ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate in a volume ratio of 1:1:1 as the electrolyte. The battery charge and discharge test was carried out in a multi-channel battery, and the test voltage range of the silicon-carbon material was 0.01V-1.5V (vs. Li+ / Li).

[0098] After the electrode materials prepared in the above Examples 1 to 7 and Comparative Examples 1 to 2 were manufactured into batteries, the main electrochemical test results were summarized as follows:

[0099] Table 1

[0100]

[0101]

[0102] From the test results of the embodiment, it can be seen that the silicon-carbon negative electrode material provided by the present invention realizes a dense structure, promotes electron transmission, and thus improves the specific energy of the material; at the same time, it also buffers the expansion of the internal material, and the smooth and uniform carbon coating layer on the outside of the material can reduce the exposed silicon on the surface and the formation of the SEI film, so that the material has a higher first efficiency and cycle stability. The obtained silicon-carbon negative electrode material has a reversible specific capacity greater than 1100mAh / g, a first cycle coulomb efficiency greater than 85%, and a capacity retention rate of more than 90% after 50 cycles. The preparation cost is low, the process is simple and controllable, and it is suitable for negative electrode materials of high-capacity lithium-ion batteries.

[0103] From the comparison between Example 1 and Comparative Example 1, it can be seen that the silicon-based composite negative electrode material obtained by the present invention has better performance. The reason is that: the present invention realizes self-crosslinking assembly in the preparation of the precursor material by adding a silane crosslinking agent, forms a three-dimensional conductive scaffold between nanographite sheets, and embeds nanosilicon, carbon nanotubes and amorphous carbon between graphite sheets, which not only plays a role in uniformly dispersing nanosilicon and carbon, but also enhances the bonding strength between nanographite sheets and amorphous materials silicon, amorphous carbon and nanotubes, and improves the adaptability of nanographite sheets in silicon-carbon negative electrode materials. Figure 1 and Figure 2 From the comparison, it can be seen that the material compounding through the chemical bond connection formed by the cross-linking reaction can significantly improve the structural strength of the synthesized composite material compared with only physical action, such as mechanical pressure. This makes the prepared silicon-carbon negative electrode material have a dense non-porous structure, increases the specific energy and electron transmission capacity, and has a stable structure.

[0104] From the comparison between Example 1 and Comparative Example 2, it can be seen that if high-temperature carbonization is directly performed without pressure treatment, pores will be formed after pyrolysis of the coated carbon, such as Figure 1 and Figure 3 As shown in the comparison. A large number of voids reduce the compaction density of the material, and also separate the various conductive agents inside the material, resulting in the inability to play a synergistic role, greatly reducing the conductivity, and thus making the reversible specific capacity low and the cycle stability poor. It can be seen that pressurization treatment plays an important role in the preparation of high-capacity negative electrode materials.

Claims

1. A lithium-ion battery silicon-carbon negative electrode material having a core-shell structure, characterized in that: The inner core contains silicon nanoparticles, graphite nanosheets, one-dimensional conductive materials and amorphous carbon; the one-dimensional conductive materials are selected from carbon nanotubes; the diameter of the carbon nanotubes is 2-20nm and the length is 1-30μm; the outer shell is a carbon coating layer; the silicon nanoparticles, carbon nanotubes and amorphous carbon are tightly embedded in the interlamellar of the evenly dispersed graphite nanosheets; The mass ratio of silicon nanoparticles, graphite nanosheets, one-dimensional conductive material, and amorphous carbon is (1-50): (1-50): (1-20): (1-10); The preparation method of silicon-carbon negative electrode material for lithium-ion batteries comprises the following steps: Step 1, dispersing graphite nanosheets and a crosslinking agent in an organic solvent to carry out a crosslinking reaction; the crosslinking agent is a silane crosslinking agent; the silane crosslinking agent is any one of dealcoholized silane, deacidified silane or deketoxime silane or a combination of at least two of them; the crosslinking agent is fully hydrolyzed and condensed to form a crosslinked product polymerized silica gel, and a graphite nanosheet dispersion having a three-dimensional crosslinked scaffold inside is obtained; Step 2, adding silicon nanoparticles, a one-dimensional conductive material, and a first carbon source to the dispersion obtained in step 1, mixing them evenly, evaporating the solvent, and applying pressure to obtain a silicon-carbon polymer; Step 3, calcining and crushing the silicon-carbon polymer; Step 4, coating with a second carbon source to obtain a negative electrode material; The first carbon source is any one or a combination of at least two of phenol, asphalt, epoxy resin, phenolic resin, furfural resin, urea-formaldehyde resin, polyvinyl alcohol, polyvinyl chloride, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, acrylic resin and polyacrylonitrile.

2. The lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: The diameter of graphite nanosheets is 10-20 μm and the thickness is 50-100 nm. The D50 particle size of silicon-carbon negative electrode materials for lithium-ion batteries is 8-24 μm and the specific surface area is 1.3 m 2 / g~6.8m 2 / g, compacted density is 1.0g / cm 3 ~1.8g / cm 3 .

3. The lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: In step 1, a pH buffer solution is also added to the organic solvent, and the pH buffer solution is a combination of one or more of acetic acid, ammonium acetate, potassium acetate, ammonia water, ammonium chloride, hypophosphorous acid, sodium hypophosphite, potassium hypophosphite, sodium carbonate or sodium bicarbonate; the pH value is 5 to 10; The crosslinking agent is a combination of one or more of methyltrimethoxysilane, vinyltriethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, triacetoxyethylsilane, propyltriacetoxysilane, n-heptyltrichlorosilane, octyltrichlorosilane, decyltrichlorosilane, dodecyltrichlorosilane, tetradecyltrichlorosilane, 1,8-bis(trichlorosilyl)octane, 1,10-bis(trichlorosilyl)decane, methyltributylacetoximate silane or vinyltributylacetoximate silane; In step 1, the organic solvent is one or a combination of at least two of tetrahydrofuran, dimethylacetamide, C1-C6 alcohol and C3-C8 ketone, the C1-C6 alcohol is one or a combination of at least two of methanol, ethanol, ethylene glycol, propanol, isopropanol, 1,2-propylene glycol, 1,3-propylene glycol, glycerol, n-butanol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, n-pentanol and 2-hexanol, and the C3-C8 ketone is one or a combination of at least two of acetone, methyl ethyl ketone, methyl propyl ketone, N-methylpyrrolidone, ethyl propyl ketone, methyl butyl ketone, ethyl n-butyl ketone, methyl amyl ketone and methyl hexyl ketone; In step 1, a constant temperature stirring device is used for heating and stirring, the heating temperature is 90-120° C., the stirring speed is 3000-6000 r / min, and the heating and stirring time is 2-5 h; the reaction process is carried out in an air environment with a humidity of 20%-60%.

4. The lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: In step 2, the D50 particle size of the silicon nanoparticles is 20 to 80 nm; In step 2, the heating temperature of the mixing process is 40-60° C., the stirring speed is 2000-5000 r / min, and the mixing time is 2-4 h; In step 2, evaporating the solvent is performed by one or more of boiling drying, vacuum drying, spray drying, suction filtration drying, freeze drying, rotary drying, infrared drying, and microwave drying; When spray drying is performed, the mixed liquid is charged into a closed spray drying device in the form of a spray, and a protective gas is charged into the closed spray drying device, wherein the protective gas is one or a combination of at least two of nitrogen, helium, argon, and neon; at the same time, the spray drying pressure is controlled to be 0.2-0.4Mpa, the inlet temperature is 100-250°C, the outlet temperature is 60-140°C, and the feed pump frequency of the spray drying equipment is 10-30Hz; Vacuum drying uses a vacuum dryer with a condensation system, the temperature condition is 50-150°C, and the vacuum negative pressure does not exceed 0.1Mpa; The pressurization treatment in step 2 is one or a combination of at least two of extrusion molding treatment, cold molding treatment, hot molding treatment and hot isostatic pressing treatment; The hot isostatic pressing treatment is to place the dried product in a hot isostatic press, pressurize and heat it to 250-400°C at 60MPa-150MPa, keep it at this temperature for 1-3 hours, then turn off the power and cool it to room temperature with the furnace. The extrusion forming process includes putting the dried product into a twin-screw machine or placing it in an internal mixer for primary compaction of the raw materials, and then performing a second compaction through a roller press.

5. The lithium-ion battery silicon-carbon negative electrode material according to claim 4, characterized in that: In step 3, during the calcination process, the temperature is first raised from room temperature to 300-400° C., kept warm for 1-2 hours, and then continued to be raised to 800-1000° C., and kept warm for 3-4 hours; the calcination is carried out in a vacuum furnace, a box furnace, a rotary kiln, a roller kiln, a push plate kiln or a tube furnace; the calcination process is carried out under a protective atmosphere, and the protective atmosphere is one or a combination of at least two of nitrogen, helium, argon and neon; In step 3, during the crushing process, the silicon-carbon polymer is crushed and classified to obtain a silicon-carbon core material with a median particle size of 8 to 40 μm; the crushing is carried out in a crusher, and the crusher is selected from at least one of a turbine crusher, a jaw crusher and a Raymond mill.

6. The lithium-ion battery silicon-carbon negative electrode material according to claim 4, characterized in that: In step 4, the coating method is selected from any one of a gas phase coating method, a liquid phase coating method or a solid phase coating method; The gas phase coating method comprises the following steps: placing the silicon carbon core material into a gas phase deposition furnace, introducing a protective gas, and then heating the material to 600-800° C. for 4-8 hours, during which an organic carbon source gas is introduced for chemical vapor deposition for 1.5-2 hours, so that a smooth and uniform carbon coating layer can be coated on the outside of the material; The steps of the liquid phase coating method are as follows: adding the silicon-carbon core material to a dispersed solvent containing a liquid phase coating carbon source, stirring and fusing, drying to obtain a coating, and then sintering the material in a protective gas furnace at a sintering temperature of 800 to 1000° C. for a high temperature sintering time of 5 to 8 hours, so that a smooth and uniform carbon coating layer can be coated on the outside of the material; The solid phase coating method comprises the following steps: mixing the silicon-carbon core material with the coating organic carbon source and placing the mixture in a coating machine for high-temperature solid phase coating to obtain a silicon-carbon solid phase coating material; then placing the silicon-carbon solid phase coating material in a carbonization furnace, introducing a protective gas, and carbonizing the furnace at a temperature of 600 to 1200° C. for 1.5 to 4 hours, and forming a smooth and uniform carbon coating layer on the outer surface of the material after natural cooling; The protective gas is one or a combination of at least two of nitrogen, helium, argon and neon; In step 4, the coated material needs to be refined and screened. The refinement method is mechanical crushing and spheroidization. The screening method is vibration screening, passing through a 200-mesh sieve, to obtain a silicon-carbon negative electrode material with a D50 particle size of 8 to 24 μm.

7. A lithium ion battery, characterized in that: It contains the lithium-ion battery silicon-carbon negative electrode material according to claim 1.

Citation Information

Patent Citations

  • A silicon-carbon composite anode material for lithium-ion batteries and its preparation method

    CN103474667B

  • Expanded graphite and nano-silicon composite material, preparation method thereof, electrode plate and battery

    CN105355870A

  • Silicon-carbon negative electrode material and preparation method thereof

    CN113394386A